Dysphagia and videofluoroscopic examination of swallowing in patients with severe motor and intellectual disabilities, and the results of dysphagia rehabilitation for these patients - Sano, Nozomi; Morimoto, Takehiko; Yano, Yoshiaki; Suzuki, Yuka; Nagao, Hideo; Watanabe, Shohei (No to hattatsu, 2007)
A dysphagia rehabilitation team at National Ehime Hospital treated fifty-seven patients with severe motor and intellectual disabilities suspected of having dysphagia. The rehabilitation team graded the degree of dysphagia by observing the patients at mealtimes. The grades were compared with the videofluoroscopic examination of swallowing results. There was some correlation with the dysphagia grades and videofluoroscopic examination of swallowing results (solid food:p = - 0.434, n =54, p < 0.0001, liquid:p = - 0.482, n = 54, p = 0.005). There were cases in which manifestations of severe dysphagia such as retention of solid food in the pharynx could only be detected on videofluoroscopic examination of swallowing. Dietary manipulation allowed shortening of the time taken at mealtimes for some patients. The dysphagia rehabilitation was useful in many cases in decreasing the number of days with fever, and improving the eating functional level, but the results as a whole were not statistically significant.